Effect of anti-PpChit1 on sand fly fitness and transmission of Leishmania infantum in American foxhounds by sand fly bite - Robles-Murguia, Maricela (Kansas State University, 2013)
Sand flies (Diptera:Psychodidae) are vectors of parasites if the genus Leishmania, the causative agent of leishmaniasis, a neglected tropical disease in several countries around the world. Sand flies transmit Leishmania to suitable vertebrates during the blood meal and following a complex development parasites undergo within the fly. Many aspects of the Leishmania development within the sand fly vector are well known, however details about how sand fly molecules affect the parasite are still not yet known. Our group previously identified that RNAi knockdown of PpChit1, a midgut specific chitinase from the sand fly Phlebotomus papatasi, led to a significant decrease in the load of Le. major. In this study, we assessed potential fitness effects of antisera anti-PpChit1 on three laboratory-reared sand fly species (P. papatasi, Phlebotomus duboscqi, and Lutzomyia longipalpis). Our results suggest that feeding sand flies with anti-PpChit1 sera led to a one day delay in the onset of oviposition, and also suggested that anti-PpChit1-fed flies survived on average up to three days longer that control flies. Analyses of the peritrophic matrix (PM) indicated a significant increase in thickness 72 hours post anti-PpChit1 feeding compared to control sera. Altogether the results suggest that feeding sand flies with anti-PpChit1 likely affects the kinetics of sand PM, which in turn affects the flow of nutrients and certain aspects of sand fly fitness. In the course of this study, we also evaluated the ability of American Foxhounds naturally infected with Leishmania infantum to transmit these parasites via bites of phlebotomine sand flies to suitable vertebrates. Since 1999, an outbreak of canine visceral leishmaniasis (CVL) has been reported in the U.S especially among Foxhounds. The ability of sand flies to pick up and transmit this pathogen represents an important health risk for companion dogs and humans. Our results indicate that Foxhounds naturally infected with Le. infantum are highly infectious to sand flies and that the parasites are able to fully develop within these vectors and de successfully transmitted during blood feeding. Thus, the risk exists for these parasites to become endemic in North America where sand flies are also known to occur.
Keywords: Sand fly; Anti-PpChit1; Fitness; Leishmania; Infection; Biology (0306); Entomology (0353)